Chicken‐or‐egg question: Which came first, extracellular vesicles or autoimmune diseases?. Issue 2 (28th February 2020) - Maione, Federica; Cappellano, Giuseppe; Bellan, Mattia; Raineri, Davide; Chiocchetti, Annalisa
Abstract: Extracellular vesicles (EVs) have attracted great interest as contributors to autoimmune disease (AD) pathogenesis, owing to their immunomodulatory potential; they may also play a role in triggering tolerance disruption, by delivering auto‐antigens. EVs are released by almost all cell types, and afford paracrine or distal cell communication, functioning as biological carriers of active molecules including lipids, proteins, and nucleic acids. Depending on stimuli from the external microenvironment or on their cargo, EVs can promote or suppress immune responses. ADs are triggered by inappropriate immune‐system activation against the self, but their precise etiology is still poorly understood. Accumulating evidence indicates that lifestyle and diet have a strong impact on their clinical onset and development. However, to date the mechanisms underlying AD pathogenesis are not fully clarified, and reliable markers, which would provide early prediction and disease progression monitoring, are lacking. In this connection, EVs have recently been indicated as a promising source of AD biomarkers. Although EV isolation is currently based on differential centrifugation or density‐gradient ultracentrifugation, the resulting co‐isolation of contaminants (i.e., protein aggregates), and the pooling of all EVs in one sample, limit this approach to abundantly‐expressed EVs. Flow cytometry is one of the most promising methods for detecting EVs as biomarkers, and may have diagnostic applications. Furthermore, very recent findings describe a new method for identifying and sorting EVs by flow cytometry from freshly collected body fluids, based on specific EV surface markers. Abstract : Review on the role of EVs in autoimmune diseases, highlighting their importance as novel biomarkers and their potential role in triggering loss of tolerance against self‐antigens.